Pengaruh Model Problem Based Learning dengan Metode Eksperimen Terhadap Hasil Belajar IPA Fisika Siswa Kelas VII SMP Negeri 19 Mataram Tahun Pelajaran 2014/2015 - Nurqomariah Nurqomariah; Gunawan Gunawan; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research is a quasi-experimental aims to find the impact of problem based learning model with experimental methods on the learning outcomes physics science of grade VII SMPN 19 Mataram in academic year 2014/2015. The population of this research is students of grade VII SMPN 19 Mataram with 144 students, while the sampling of this research is grade as VIIA as experimental group and VIIB as the control group. The sampling technique used is purposive sampling. The research design used is untreated control group design with pretest and posttest. Pre-test results obtained by the average value of experimental group is 25.36 while the control group is 28.54. Post-test results for experimental group is 75.13, while for the control group is 65.41. Research hypotheses were analyzed by t-test two tail using formulas polled variance t-test given the result that thint is greater than ttable, In addition, an increase on learning outcomes analyzed using N-gain test given the result that experimental group has increased higher than the control group.so that can be concluded that the model of problem-based learning with experimental method given positive impact on learning outcomes physics science of grade VII SMPN 19 Mataram in academic year 2014/2015.